A dynamic state observer to control the energy consumption in aluminium production cells. Issue 1 (1st January 2016) - Braga, Carlos Augusto P.; da Fonseca Netto, Joao Viana
ABSTRACT: The debate about the future of the aluminium industry often concentrates on the high energy usage associated with aluminium production. A combination of breakthroughs in advanced control systems and straight-out innovation are focused on improving the overall energy costs on aluminium reduction smelters. This paper presents the development and real-time evaluation of a state-space observer based on Kalman filtering design to control the energy consumption inside the aluminium production cell, leading to a lower consumption of energy and to a better process control. The new control system is able to handle the plant dynamics, working in a control loop that is arranged in such a fashion to try to regulate the electricity usage during the electrolysis process by regulating the anode-to-cathode distance. From process control perspective this approach can overcome various types of abnormal conditions that affect the cell energy consumption and the cell stability. From production cost perspective, the proposed methodology contributes to maximize the energy savings.